Cotranslational assembly of protein complexes in eukaryotes revealed by ribosome profiling - Shiber, Ayala; Döring, Kristina; Friedrich, Ulrike A.; Klann, Kevin; Merker, Dorina; Zedan, Mostafa; Tippmann, Frank; Kramer, Günter; Bukau, Bernd (Nature, 2018)
Cotranslational assembly is a prevalent mechanism for the formation of oligomeric complexes in Saccharomyces cerevisiae, with one subunit serving as scaffold for the translation of partner subunits.
Das PDF enthält einen Anhang von 17 ungezählten Seiten
Gesehen am 31.10.2018